Lifecycle management model review and design for LSP - Sunida Tiwong (2018)
© 2018 Association for Computing Machinery. Although Logistics Service Providers (LSP) are crucial in today global business, not many logistics companies are able to sustain the high competitiveness in this opening economy. The adoption of a service lifecycle is expected to create adding value for LSPs to connect and strengthen relationship with their customers. Whilst the lifecycle management model for LSP is not existed, literatures are reviewed including Product Service System (PSS), Service Lifecycle Management (SLM) and Product Lifecycle Management (PLM). The Service Lifecycle will focus on the lifecycle of the services from the Beginning of Life, Middle of Life to the End of Life in term of activity and relationship. Service lifecycle management can be long-term, considering more than a product that just focuses on design, operation, spare part, overhaul and disposal. The model shall focus on customer and supplier to maintain the performance of service, to uses the full-service contract to response customer satisfaction. Besides, the strategies and tactic of the logistics service provider are important to response customer requirement.